Inclusion of Health Care Forensics in Medical Education: Ethical, Legal and Educational Challenges in Identifying and Providing Patient-Centered Care for Victims of Child Abuse, Neglect and Human Trafficking - Mora , Annalee; Chance, Cheryl; Tulp, Orien L. (Research Highlights in Disease and Health Research Vol. 4, 2023)
The prevalence of child abuse and human trafficking in human existence has occurred in various forms for many centuries and now appears to be approaching epidemic proportions in many societies where borders are insecure and enforcement resources are inadequate. The emergence of child abuse and human trafficking in their different forms is a serious crime that affects virtually every country in the world, where they not only represent a violation of the basic human rights and dignity of those impacted, but also have an impact on their families and loved ones who may be inadvertently left behind. While the majority of cases of human trafficking have traditionally involved humans being coercively forced to engage in sex and labor violations, an emerging area of illegal organ trafficking to support an increasing need for organ transplantation procedures can now be included. While children and young adults are the most frequently affected segments of the population for some types of trafficking, human trafficking can affect victims of any age, gender, race, ethnicity, culture, or persuasion, and they can reveal in the clinic accompanied or unaccompanied for urgent care. When presenting, a patient may display cardinal signs, symptoms, and clinical stigmata that are of a suspicious nature and suggest further investigation, including reporting the issues to competent authorities, especially if the victim is an infant or regarded a minor, less than 18 years of age in most countries. Since health care professionals are frequently the first point of contact when symptoms and stigmata of human trafficking, child abuse, and other signs of abuse are evident, additional modules in health care forensics would be a welcome addition to medical curricula and public health perspectives for physicians and other members of the healthcare team. Thus, the goal of this paper was to review the characteristics of human trafficking and abuse, to summarize key areas of legal, medical, and administrative responsibility in order to ensure the availability of optimal and appropriate patient-centered care for victims, and to emphasize the significance of including modules in forensic medical education in medical curricula.